The academic basis of primary health care - Greenhalgh, Trisha (Henry Stewart Talks, 2018)
What is primary health care?, Why does primary health care matter?, Starfield: primary care assessment tool, Academic disciplines of primary health care, Social and cultural influences on health, New research priorities